2021
DOI: 10.1161/strokeaha.120.033152
|View full text |Cite
|
Sign up to set email alerts
|

Residual Inflammatory Risk Predicts Poor Prognosis in Acute Ischemic Stroke or Transient Ischemic Attack Patients

Abstract: Background and Purpose: It is still unclear whether the residual cholesterol and inflammatory risk in the acute phase is associated with prognosis of stroke. We aimed to investigate the proportion and relative contribution of residual cholesterol and inflammatory risk, determined by baseline low-density lipoprotein cholesterol (LDL-C) and high-sensitivity C-reactive protein (hsCRP) levels, to the risk of recurrent stroke and poor functional outcome at 1 year. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Patients with no hsCRP measurements or only one blood hsCRP measurement were excluded from the analysis. High inflammatory status was defined as hsCRP ≥3 mg/l according to previous studies [4,10,12]. Patients were classified into four groups according to two hsCRP values at baseline and 3 months: (i) persistent high RIR-high values of hsCRP at baseline and 3 months; (ii) attenuated RIR-high hsCRP at baseline and low hsCRP at 3 months; (ii) increased RIR-low hsCRP at baseline and high hsCRP at 3 months; and (iv) persistent low RIR-low hsCRP values at baseline and 3 months.…”
Section: Blood Sample Collection and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with no hsCRP measurements or only one blood hsCRP measurement were excluded from the analysis. High inflammatory status was defined as hsCRP ≥3 mg/l according to previous studies [4,10,12]. Patients were classified into four groups according to two hsCRP values at baseline and 3 months: (i) persistent high RIR-high values of hsCRP at baseline and 3 months; (ii) attenuated RIR-high hsCRP at baseline and low hsCRP at 3 months; (ii) increased RIR-low hsCRP at baseline and high hsCRP at 3 months; and (iv) persistent low RIR-low hsCRP values at baseline and 3 months.…”
Section: Blood Sample Collection and Measurementsmentioning
confidence: 99%
“…Indeed, CRP is relatively stable in healthy individuals [11] but can be increased transiently as an acute phase reactant. Our recent study showed that baseline RIR was associated with 1‐year stroke recurrence and poor functional outcome [12]. A previous study showed that longitudinal increases in hsCRP were also associated with an increased risk of adverse cardiovascular outcomes in patients with acute coronary syndrome [13].…”
Section: Introductionmentioning
confidence: 99%
“…Programed death-ligand 1 (PD-L1) is a membrane-bound protein that exerts immune checkpoint roles by binding to programed death-1 (PD-1) receptor; PD-L1 has long been known for its involvement in escaping immune surveillance of tumor cells. 7,8 Recent report identified PD-L1 released by tumor cells into the circulation to mediate systemic immunosuppression. 8 We here find that neurons of healthy humans and mice express high basal levels of PD-L1, which are significantly reduced in the perihematomal area upon hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical evidence and laboratory evidence suggested that anti-inflammatory therapies effectively decreased vascular damages and suppressed cerebral ischemic stroke (Kelly et al, 2018). Moreover, a high level of residual inflammatory risk (RIR) was proven to imply patients' poor prognosis of acute cerebral ischemic stroke (Li et al, 2021a), while high-sensitivity C-reactive protein (hs-CRP), which represented early inflammatory response, was addressed as a decisive factor of RIR (Ridker et al, 2017). Low-level inflammation reflected by hs-CRP indicated recurrent ischemic events independently (Mengozzi et al, 2020;Coveney et al, 2021).…”
Section: Introductionmentioning
confidence: 99%